THE IMPORTANCE OF THE DRUG ARTOXAN (Ta'limning zamonaviy transformatsiyasi, 2024)
A comparative analysis of the use of artoxan in injection form and with interstitial electrophoresis in patients with acute vertebrogenic lumbosacral radiculopathic pain was carried out. The objectification of treatment effectiveness is based on clinical and neurological data and VAS. Interstitial electrophoresis of artoxan significantly improves the results of treatment of the disease compared to its parenteral administration, due to potentiation of the therapeutic properties of galvanic current and medication.